Hubungan Perilaku Manusia dengan Kejadian Malaria di Desa Daiama Wilayah Kerja Puskesmas Sotimori Kecamatan Landu Leko Kabupaten Rote Ndao - Carolin Florinia Rangku; Yuliana Radja Riwu; Tanti Rahayu (Yayasan Literasi Sains Indonesia, 2024)
Malaria is an infectious disease caused by the Plasmodium genus transmitted to humans through the bite of female Anopheles mosquitoes. Behavioral factors Humans also play an important role in the emergence of a disease, behavioral factors humans consist of the habit of using mosquito nets, the habit of using drugs mosquitoes, the habit of hanging clothes, and the habit of going outside at night day. In 2022, the incidence of malaria in Rote Ndao Regency will increase namely, there were 253 cases and the most cases were in Landu sub-district In particular, in Daiama Village there were 95 cases. The aim of this research is to analyze the relationship between human behavioral factors and events malaria in Daiama Village, Sotimori Health Center working area, Landu Leko District Rote Ndao Regency. This type of research is an analytical survey, with a case design control. The total sample was 92 people selected using simple random techniques example. The results of bivariate analysis using the chi-square test show that there is significant relationship between the habit of using mosquito nets (p-value=0.000), habit of using mosquito repellent (p-value=0.0019), habit of hanging clothing (p-value=0.0021) and the habit of leaving the house at night (p-value=0.0030) with the incidence of malaria. It is hoped that health workers who is at the Sotimori Community Health Center providing education to the community in a way carry out outreach in order to increase public knowledge about malaria and how to prevent malaria.